The Association Between Quantitative Flow Ratio and Intravascular Imaging-defined Vulnerable Plaque Characteristics in Patients With Stable Angina and Non-ST-segment Elevation Acute Coronary Syndrome - Zuo, Wenjie; Sun, Renhua; Zhang, Xiaoguo; Qu, Yangyang; Ji, Zhenjun; Su, Yamin; Zhang, Rui; Ma, Genshan (Frontiers in Cardiovascular Medicine, 2021)
Background: This study aimed to examine whether quantitative flow ratio (QFR), an angiography-based computation of fractional flow reserve, was associated with intravascular imaging-defined vulnerable plaque features, such as thin cap fibroatheroma (TCFA) in patients with stable angina, and non-ST-segment elevation acute coronary syndrome. Methods: Patients undergoing optical coherence tomography (OCT) or intravascular ultrasound (IVUS) examinations were identified from two prospective studies and their interrogated vessels were assessed with QFR. Lesions in the OCT cohort were classified into tertiles: QFR-T1 (QFR ≤ 0.85), QFR-T2 (0.85 < QFR ≤ 0.93), and QFR-T3 (QFR > 0.93). Lesions in the IVUS cohort were classified dichotomously as low or high QFR groups. Results: This post-hoc analysis included 132 lesions (83 for OCT and 49 for IVUS) from 126 patients. The prevalence of OCT-TCFA was significantly higher in QFR-T1 (50%) than in QFR-T2 (14%) and QFR-T3 (19%) (p = 0.003 and 0.018, respectively). Overall significant differences were also observed among tertiles in maximum lipid arc, thinnest fibrous cap thickness, and minimal lumen area (p = 0.017, 0.040, and <0.001, respectively). Thrombus was more prevalent in QFR-T1 (39%) than in QFR-T2 (3%), and QFR-T3 (12%) (p = 0.001 and 0.020, respectively). In the multivariable analysis, QFR ≤ 0.80 remained as a significant determinant of OCT-TCFA regardless of the presence of NSTE-ACS and the level of low-density lipoprotein cholesterol (adjusted OR: 4.387, 95% CI 1.297–14.839, p = 0.017). The diagnostic accuracy of QFR was moderate in identifying lesions with OCT-TCFA (area under the curve: 0.72, 95% CI 0.58–0.86, p = 0.003). In the IVUS cohort, significant differences were found between two groups in minimal lumen area and plaque burden but not in the distribution of virtual histology (VH)-TCFA (p = 0.025, 0.036, and 1.000, respectively). Conclusions: Lower QFR was related to OCT-defined plaque vulnerability in angiographically mild-to-intermediate lesions. The QFR might be a useful tool for ruling out high-risk plaques without using any pressure wire or vasodilator.